Kinematic analysis and energy saving optimization design of parallel lifting mechanism for stereoscopic parking robot - Jingang Jiang; Dianhao Wu; Tianhua He; Yongde Zhang; Changpeng Li; Hai Sun (Energy Reports, 2022)
The application of the stereoscopic parking robot makes it possible to relieve the pressure of urban traffic efficiently. With the aggravation of energy and environmental problems, the energy consumption of the stereoscopic parking robot is mainly concerned. In robot design, the kinematic performance reflects the motion transfer capability of the mechanism. A reasonable size of the mechanism can make energy transfer more efficient. This paper proposes a 2-DOF (Degree of Freedom) parallel lifting mechanism of the stereoscopic parking robot. Its branch contains double-constrained triangles that can perform symmetrical movements. Forward kinematics, inverse kinematics, workspace, and singular configuration are studied and analyzed. In this scheme, depending on the characteristics of the mechanism, the evaluation indices of motion consistency, workspace, and singularity performance are proposed. The energy-saving optimization design method based on the multiple kinematic performance indexes is used to find the optimum combination of structural parameters in the feasible region. Finally, the parallel lifting mechanism prototype is constructed, and the dynamic verification experiments are performed at driving speeds of 15.625, 12.5, and 10.42 mm/s. The results provide helpful guidance for the choice of driving speed to achieve optimal movement transfer capacity and stability of the mechanism. The multiple performance index design method can also be applied to other parallel mechanisms with low mobility, which require energy savings and steady motion.